IMPROVING THE ABRASION RESISTANCE OF STEELS BY FORMING HETEROGENEOUS ELECTROSPARK COATINGS - Mikosianchyk, Oksana; Shamrai, Vitaliy; Yashchuk, Olesia; Lopata, Oleksandr; Mnatsakanov, Stepan; Hanziak, Olena (Problems of Friction and Wear, 2026)
The work is dedicated to increasing the operational life of agricultural machinery parts operating under conditions of intensive dynamic and abrasive environmental impact. The aim of the study is to determine the effect of continuity, microstructure, and phase composition of heterogeneous composite electrospark coatings based on tungsten and chromium carbides on their abrasive wear resistance. Surface modification of specimens made of 65G and 40X13 steels was carried out by electrospark alloying on "Elitron-22" micro-welding equipment using a VK8 tungsten-cobalt system electrode and a KHN25 chromium carbide-nickel system powder mixture, respectively. Tribological stability tests were conducted in an environment of loose silicon carbide abrasive particles according to an adapted procedure of the ASTM G65 standard. According to the analysis results, regular changes in the chemical composition of the formed coatings were recorded compared to the initial anode materials. An increased cobalt content of up to 12.6 wt. % was detected in the tungsten carbide-cobalt system, which is due to its preferential melting under the action of pulsed discharges with the formation of a developed surface matrix. For the chromium carbide-nickel system, a decrease in chromium concentration to 55.8 wt. % was determined due to thermal burnout, with relative stability of the nickel binder, which was 26.8 wt. %. The wear kinetics assessment showed that the minimum weight loss of both types of coatings is achieved at their continuity of 55–75%. At the same time, the KHN25 electrospark coating demonstrates 1.8–2.0 times higher wear resistance compared to VK8. The higher abrasive resistance of the KHN25 coating is explained by its fine-grained structure and the presence of a ductile nickel matrix, which provides effective relaxation of local stresses and inhibits brittle chipping of carbide phases during micro-cutting by the abrasive.